Detoxification and benefits on acute heart failure in mice- of fuziline using glycyrrhetinic acid: an integrated biochemical analysis - Chang, Nianwei; Hou, Chunyu; Zhai, Yue; Zhang, Wenying; Hu, Zengmei; Wang, Xiaoying (Frontiers in Pharmacology, 2024)
Introduction: Aconiti Lateralis Radix Praeparata (lateral roots of Aconitum carmichaelii Debeaux, Fuzi), is commonly used to treat various cardiovascular diseases, particularly heart failure. However, its strong cardiotoxicity limits its clinical applicability. Glycyrrhizae radix et rhizoma, (the root of Glycyrrhiza uralensis Fisch., Gancao), is known to synergistically increase the cardiotonic effects of Fuzi and alleviate the myocardial injury caused by Fuzi to some extent. However, the detailed mechanism via which the combination of Fuzi and Gancao reduces toxicity and increases or preserves the efficacy of Fuzi requires further investigation. Methods: Oxidative stress injury models in H9C2 cells and mice with acute heart failure were established to evaluate the optimal synergistic protective concentration of Fuziline and Glycyrrhetinic acid (GA). A GA probe was then synthesized and used for target fishing using chemical and biological methods. Finally, the target and its function were verified using fluorescence co-localization, western blotting, protein interaction analysis, molecular docking, and calcium ion imaging. Results: The best pharmacodynamic potential was achieved with a 1:1 or 2:1 ratio of Fuziline and GA concentrations. At these ratios, they regulated the protein levels of the downstream players of the Ca 2+ signaling pathway via MDH2 and CALR, thereby balancing Ca 2+ homeostasis in the myocardial tissue and mitigating the effects of heart failure.This study aimed to investigate the compatibility of Fuziline and GA, the active metabolites of a traditional Chinese medicine (TCM) pair, in exerting their cardiac effects, identify the direct biological targets and verify the mechanism of compatibility.